San Lorenzo Urban Memory Museum – Slumm Mapcast - Macchia, Andrea; Rivaroli, Laura; Fiacconi, Marta; Rivaroli, Marta; Donnini, Alessandra (Ge-conservacion, 2017)
It is possible to create a museum where there are libraries instead of bookshops, craft shops instead of gift shops, where the employees are the citizens, the educational projects and the night events are linked together and art is a vehicle for narration and regeneration. This is SLUMM, San Lorenzo Urban Memory Museum. The aim of the museum is to preserve San Lorenzo memories and to address its social, political and cultural transformations through the voices and the memories of the people and the places. One of the approaches used by SLUMM is the use of the mobile app Mapcast, created by Etcware SRL, for the creation of personalised cultural itineraries. The users can select the quality of the material and add their own information in order to integrate the content and to be actively involved in the creation of culture and knowledge.